Science at the end of empire Experts and the development of the British Caribbean, 1940-62 - Clarke, Sabine (Studies in Imperialism, 2018)
This book produces a major rethinking of the history of development after 1940 through an exploration of Britain's ambitions for industrialisation in its Caribbean colonies. Industrial development is a neglected topic in histories of the British Colonial Empire, and we know very little of plans for Britain's Caribbean colonies in general in the late colonial period, despite the role played by riots in the region in prompting an increase in development spending. This account shows the importance of knowledge and expertise in the promotion of a model of Caribbean development that is best described as liberal rather than state-centred and authoritarian. It explores how the post-war period saw an attempt by the Colonial Office to revive Caribbean economies by transforming cane sugar from a low-value foodstuff into a lucrative starting compound for making fuels, plastics and medical products. In addition, it shows that as Caribbean territories moved towards independence and America sought to shape the future of the region, scientific and economic advice became a key strategy for the maintenance of British control of the West Indian colonies. Britain needed to counter attempts by American-backed experts to promote a very different approach to industrial development after 1945 informed by the priorities of US foreign policy.